2005
DOI: 10.1177/154405910508400405
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gingival Fibroblast Minocycline Accumulation by Biological Mediators

Abstract: Gingival fibroblasts actively accumulate tetracyclines, thereby enhancing their redistribution from blood to gingiva. Since growth factors and pro-inflammatory cytokines regulate many fibroblast activities, they could potentially enhance fibroblast minocycline accumulation. To test this hypothesis, we treated gingival fibroblast monolayers for 1 or 6 hours with platelet-derived growth factor-BB (PDGF), fibroblast growth factor-2 (FGF), transforming growth factor-β1 (TGF), or tumor necrosis factor-α (TNF). Mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This enhancement by TNF could potentially contribute to enhanced NSAID accumulation by fibroblasts in inflamed gingiva. A similar pattern of enhancement by TNF-αhas been reported with respect to minocycline transport by gingival fibroblasts (Walters et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…This enhancement by TNF could potentially contribute to enhanced NSAID accumulation by fibroblasts in inflamed gingiva. A similar pattern of enhancement by TNF-αhas been reported with respect to minocycline transport by gingival fibroblasts (Walters et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…5). Previous studies have shown that human gingival fibroblasts display an active transport mechanism for minocycline uptake (3,14). In cultured ARVF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Minocycline transport in cardiac cells was measured fluorometrically in each seeded well as described (3,14) with modifications. Briefly, culture plates containing cell monolayers were washed 4× with Hank's Balance Salt Solution (HBSS), overlaid with HBSS and warmed to 37°C prior to assay.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of antimicrobial efficacy, tetracyclines have different affinities for the 30S bacterial ribosomal subunits resulting in different therapeutic efficacies [27]. Little information is available on the uptake and release of tetracyclines by mammalian cells [28,29] and no data are available for uptake by J774 cells. This is the first report to show that the new tetracycline compound tigecycline is able to inhibit LPS-induced nitric oxide production and release from macrophages.…”
Section: Discussionmentioning
confidence: 99%